Instrument grading of beef - Vote, Derek Jason, author; Belk, Keith, advisor (Colorado State University. Libraries, 2003)
A study was conducted to determine the viability of the VIAscan Beef Carcass System (BCS) and/or Computer Vision System equipped with a BeefCam module (CVS BeefCam) to predict the fabrication yields of Uruguayan beef carcasses and the CVS BeefCam to segregate Uruguayan beef carcasses into groups that differ in Warner- Bratzler shear force (WBSF) values. Uruguayan National Institute of Meat (INAC) grades, USDA yield grade, CVS BeefCam, BCS, and combined CVS BeefCam and BCS output, respectively, accounted for 1) 35, 37, 41, 49, and 53% of the variation in commodity trimmed saleable meat yield (SMY); 2) 36, 41, 45, 52, and 58% of the variation in closely trimmed SMY; 3) 37, 52, 55, 58, and 66% of the variation in very closely trimmed SMY; and 4) 36, 53, 57, 59, and 69% of the variation in extra closely trimmed SMY. Correlation coefficients between WBSF values and CVS BeefCam output variables for lean color obtained approximately 50 min after ribbing were larger when carcasses considered to be dark cutters by visual appraisal were excluded rather than included. Output variables from the CVS BeefCam including lean L*, a*, and b* collected for steer and heifer carcasses (n = 178) and lean L*, a*, b*, and fat L* collected for mature cow carcasses (n = 107), were effective for segregating carcasses not considered to be dark cutters by visual appraisal into groups that differed (P < 0.05) in WBSF values. Classification of carcasses using CVS BeefCam output variables could help identify more uniform groups of steaks with respect to tenderness from Uruguayan beef carcasses. Another study was conducted to determine if reflectance measurements made in the near-infrared region of the spectrum were additive to reflectance measurements made in the visible region of the spectrum for predicting WBSF values. Reflectance measurements obtained in the near-infrared region of the spectrum were correlated with WBSF values, however, these measurements were not additive to the predictive ability of reflectance measurements made in the visible portion of the spectrum when the use of broad-band wavelength filters were simulated.
Keywords: food science